Sensory deficits in ipsilesional upper-extremity in chronic stroke patients - Núbia Maria Freire Vieira Lima; Karina Cândido Menegatti; Érica Yu; Natália Yumi Sacomoto; Thais Botossi Scalha; Illia Nadinne Dantas Florentino Lima; Saionara Maria Aires da Camara; Marcelo Cardoso de Souza; Roberta de Oliveira Cacho; Enio Walker de Azevedo Cacho; Donizeti Cesar Honorato (Arquivos de Neuro-Psiquiatria)
Objective To investigate somatosensory deficits in the ipsilesional wrist and hand in chronic stroke patients and correlate these deficits with contralesional sensorimotor dysfunctions, functional testing, laterality and handedness.Methods Fifty subjects (twenty-two healthy volunteers and twenty-eight stroke patients) underwent evaluation with Semmes-Weinstein monofilaments, the sensory and motor Fugl-Meyer Assessment, the Nottingham Sensory Assessment in both wrists and hands and functional tests.Results Twenty-five patients had sensory changes in the wrist and hand contralateral to the stroke, and eighteen patients (64%) had sensory deficits in the ipsilesional wrist and hand. The most significant ipsilesional sensory loss was observed in the left-handed patients. We found that the patients with brain damage in the right hemisphere had better scores for ipsilesional tactile sensation.Conclusions A reduction in ipsilesional conscious proprioception, tactile or thermal sensation was found in stroke subjects. Right hemisphere damage and right-handed subjects had better scores in ipsilesional tactile sensation.